Effects of hydrophobic core components in amphiphilic PDMAEMA nanoparticles on siRNA delivery. (April 2015) - Han, Shangcong; Cheng, Qiang; Wu, Yidi; Zhou, Junhui; Long, Xingwen; Wei, Tuo; Huang, Yuanyu; Zheng, Shuquan; Zhang, Jianhua; Deng, Liandong; Wang, Xiaoxia; Liang, Xing-Jie; et al.
Abstract: Due to their biodegradable character, polyesters such as polycaprolactone (PCL), poly(d, l -lactide) (PDLLA), and polylactic-co-glycolic acid (PLGA) were widely used as the hydrophobic cores of amphiphilic cationic nanoparticles (NPs) for siRNA delivery. However, fewer researches focused on facilitating siRNA delivery by adjusting the polyester composition of these nanoparticles. Herein, we investigated the contribution of polyester segments in siRNA delivery in vitro by introducing different ratio of DLLA moieties in PCL segments of mPEG-block-PCL-graft-poly(dimethylamino ethyl methacrylate)(PEG-b-PCL-g-PDMAEMA). It was noticed that compared with the other ratios of DLLA moieties, a certain molar ratio (about 70%) of the NPs, named mPEG45 -P(CL21 -co-DLLA48 )-g-(PDMAEMA29 )2 (PECLD-70), showed the highest gene knockdown efficiency but poorest cellular uptake ability in vitro. Further research revealed that NPs with various compositions of the polyester cores showed different physicochemical properties including particle size, zeta potential and stiffness, leading to different endocytosis mechanisms thus influencing the cellular uptake efficiency. Subsequently, we observed that the cells treated by PECLD-70 NPs/Cy5 siRNA complexes exhibited more diffuse Cy5 signal distribution than other NPs by confocal laser scanning microscope, which suggested that siRNA delivered by PECLD-70 NPs/Cy5 siRNA complexes possessed of stronger capabilities in escaping from endosome/lysosome, entering the RNA-induced silencing complex (RISC) and cutting the target mRNA efficiently. The different siRNA release profile was dominated by the degradation rate of polyester segments. Therefore, it could be concluded that the adjustment of hydrophobic core of cationic nanoparticles could significantly affect their transfection behavior and appropriate polyester composition should be concerned in designing of analogous siRNA vectors.